2004
DOI: 10.1158/0008-5472.can-03-2285
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Retinoic Acid Treatment Induces Sodium/Iodide Symporter Expression and Radioiodide Uptake in Mouse Breast Cancer Models

Abstract: Lactating breast tissue and some breast cancers express the sodium/ iodide symporter (NIS) and concentrate iodide. We recently demonstrated that all-trans retinoic acid (tRA) induces both NIS gene expression and iodide accumulation in vitro in well-differentiated human breast cancer cells (MCF-7). In the present study, we investigated the in vivo efficacy and specificity of tRA-stimulated iodide accumulation in mouse breast cancer models. Immunodeficient mice with MCF-7 xenograft tumors were treated with syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
2
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 56 publications
2
62
2
1
Order By: Relevance
“…In addition, significant induction of NIS mRNA and protein expression and markedly increased iodide accumulation was demonstrated in vivo in xenograft tumors after atRA treatment [9][10][11]. Based on those studies, we and other demonstrated a stimulatory effect on atRA-induced NIS expression in MCF-7 cells by the addition of glucocortiocoids [10,13,14].…”
Section: Mcf-7 Cells In Vitrosupporting
confidence: 53%
See 1 more Smart Citation
“…In addition, significant induction of NIS mRNA and protein expression and markedly increased iodide accumulation was demonstrated in vivo in xenograft tumors after atRA treatment [9][10][11]. Based on those studies, we and other demonstrated a stimulatory effect on atRA-induced NIS expression in MCF-7 cells by the addition of glucocortiocoids [10,13,14].…”
Section: Mcf-7 Cells In Vitrosupporting
confidence: 53%
“…All-trans retinoic acid (atRA) has been demonstrated to induce both NIS gene expression as well as iodide accumulation in vitro in a well-differentiated estrogen receptorpositive human breast cancer cell line (MCF-7), which has also been confirmed in mouse breast cancer models in vivo [9][10][11][12]. In more recent studies, we and others have demonstrated that dexamethasone (Dex) is able to significantly enhance atRA-induced NIS expression and iodide accumulation in MCF-7 cells in vitro and in vivo [10,[13][14][15].…”
Section: Introductionmentioning
confidence: 96%
“…The first of these is SLC26A4, which encodes for the pendrin (PDS) expressed in apical membranes and has been suggested to transfer iodide into the colloid from the cells. It has previously shown that PDS expression was detected in thyroid (B-CPAP), thyroid cancer (WRO, FRO, ARO) [27] and breast cells (MCF-7) [28]. The other is SLC5A8 (human apical iodide transporter, hAIT), which was suggested to charge the release of iodide into the colloid across the apical membrane as an iodide channel [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…A large number of agents with very different mechanisms of action have been utilized to stimulate NIS expression, such as redifferentiating agents [12,15,[33][34][35], or compounds that are reported to physiologically regulate NIS in breast cells [7,[36][37][38]. Retinoid acid, especially in the presence of other compounds such as dexamethasone, induce NIS and iodide uptake in breast cancer cells [12,15,[33][34][35] and in animal models [39]. Even though these findings suggest their potential clinical use, as yet no clinical trials have been presently designed to this aim and additional strategies can be foreseen.…”
Section: Discussionmentioning
confidence: 99%